2014
DOI: 10.4236/oji.2014.42008
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of and Risk Factors for Cytomegalovirus among HIV-Infected Patients at University of Maiduguri Teaching Hospital, Nigeria

Abstract: Although the distribution of cytomegalovirus (CMV) infection has a wide regional variation, it is more common in Africa and Asia with high prevalence approaching 100% in some communities. CMV is a frequent opportunistic infection and major cause of morbidity and mortality among HIV patients with severe immunosuppression. It can be contracted from body fluid, including saliva, urine, blood, cervical secretions, and semen. CMV seropositivity is considered the best laboratory measure of past infection. We determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Similarly, 93.9% seroprevalence was reported by Fowotade et al21 among HIV patients in Ilorin. Yet higher prevalence rates for CMV IgG antibodies have been reported among HIV patients by Ojide et al23 and Kida et al32 in Benin, Edo state and Maiduguri, Borno state respectively. Elsewhere outside the country, prevalence of 77.3%25 and 90.0%-100.0%33,34 were reported from Kenya and India respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, 93.9% seroprevalence was reported by Fowotade et al21 among HIV patients in Ilorin. Yet higher prevalence rates for CMV IgG antibodies have been reported among HIV patients by Ojide et al23 and Kida et al32 in Benin, Edo state and Maiduguri, Borno state respectively. Elsewhere outside the country, prevalence of 77.3%25 and 90.0%-100.0%33,34 were reported from Kenya and India respectively.…”
Section: Discussionmentioning
confidence: 84%
“…A total of 84(93.3%, 95% CI: 88-98.5) sera had specific HCMV IgG antibodies while only 2(2.3% 95% CI: 0.8-5.4) had specific HCMV IgM antibodies. Higher rates of HCMV IgG seroprevalence have been similarly observed elsewhere among HIV infected individuals [ 14 , 15 ]. In comparison to previous studies the reported prevalence of HCMV IgM antibodies was lower [ 16 ].…”
Section: Briefmentioning
confidence: 74%
“…[1][2][3][4][5] By adulthood, most people in developing countries like Nigeria are said to have had primary HCMV infection, with some studies reporting up to 100% prevalence of anti-HCMV IgG, a marker of previous infection, among immunocompetent individuals. 3,[6][7][8][9] Nigeria has one of the largest number of people living with HIV/AIDS (PLWHA). 10 Reactivation of latent HCMV infection in immunosuppressed individuals leads to viraemia, dissemination of the virus, and end-organ diseases (EODs), such as retinitis, colitis, pneumonitis and encephalitis.…”
Section: Introductionmentioning
confidence: 99%